Groundwater quality assessment in western Saudi Arabia using GIS and multivariate analysis - Fahad Alshehri; Abdelbaset S. El-Sorogy; Sattam Almadani; Mufleh Aldossari (Journal of King Saud University: Science, 2023)
In arid and semi-arid regions, assessment of groundwater quality and potentially toxic elements is essential issue for health of the human being. Groundwaters were collected from sixty-eight wells in Harrat Khaybar, Saudi Arabia to evaluate their suitability for drinking and irrigation purposes and to document the potential sources of contamination. Several contamination indices and inverse distance weighted technique were applied for assessing contamination and generate spatial maps for the potentially toxic elements (PTEs). The results showed that the average values of the ions, Cl–, SO42–, HCO3–, NO3–, Na+, Ca2+, Mg2+, and the total dissolved solids (TDS) were greater than the permissible limit for drinking water while the average values of PTEs were less than the permissible limit, with exceeding limits of Cr, Se, As, Zn, and Pb in some individual samples. Piper diagram indicated that 47.10% of the water samples are of Na-K-SO4-Cl type, 23.51% of Ca-Mg-CO3-HCO3 type, 23.51% of Ca-Mg-SO4-Cl type, and 5.88% of Na-K-CO3-HCO3 type. Based on the groundwater quality index (GWQI), 29 of the groundwater wells were categorized as excellent and good water for drinking purposes, while 29 wells fell under poor, very poor water, and unsuitable for drinking. Additionally, results of heavy metal pollution index (HPI) indicated that all waters fell within the low pollution category, while results of the metal index (MI) indicated that 35 wells fell within very pure, pure, and slightly affected categories, while 33 wells fell in the moderately, strongly, and seriously affected categories. Results of sodium adsorption ratio (SAR), sodium percentage (%Na), and magnesium ratio (MR) revealed that 33.82–98.5 % of the water samples are suitable for irrigation depending on the parameter type. Ions exchange reactions and dissolution of rock forming minerals, as well as industrial and domestic effluents and intensive use of fertilizers and pesticides were the natural and anthropogenic factors controlling the groundwater geochemistry in the study area and PTE contamination in some wells.